O42-4 Innovative exposure assessment scheme to assess health impact of outdoor air pollution in new delhi. (1st September 2016) - Joshi, Tushar Kant
Abstract : New Delhi, Capital city of India has been experiencing a steady increasing level of outdoor air pollution over a period of two decades as demonstrated by Monitoring Programme following the enactment of e Air (Prevention and Control of Pollution) Act, 1981. The levels of PM10 and PM2.5 have now reached alarming levels. The concern grew further after the monitoring of PM2.5 was initiated. According to the Global Burden of Disease Report, Outdoor air pollution has become the fifth largest killer in India. An epidemiological study was undertaken to assess the association between the adverse health outcomes and the air pollution in New Delhi. A total of 1073 adults and 903 adolescents were randomly chosen. Assessment of exposure was done by adding up the total hours spent outdoors by rural and urban residents. The average exposure to vehicular pollution in urban subjects was nearly three times that of rural population. A questionnaire was developed, validated and administered by trained surveyors along with the measurement of height, weight and blood pressure. Results: The urban subjects experienced significantly more symptoms on the day of survey, and in last one year but it was the rural subjects who experienced more symptoms following exposure to air pollution proving that urban subjects probably developed tolerance following persistent exposure. Such tolerance has been earlier reported by investigators to ozone in particular in North America. The results also showed that those with pre existing heart disease and respiratory disorders like asthma, reported significantly more chest – tightness, respiratory infections, and dyspnoea than those not having such disorders. The adverse impact were also more pronounced in adolescent subjects affecting their attendance and performance in school. This paper would share findings of the adverse health impact of the air pollution on Delhi's residents reported for the first time.